Industrial detergent wastewater treatment via fenton reagent - Mohd Zairie, Mohd Yusuff (2010)
Production of detergent can generates wastewater containing organics matter with will consume an oxidation demand, surfactants,suspended solids,fat and oil. Besides,sulfate concentration is high in the most detergent plant effluent because of the sulphonation process that has physiological and toxic effects on marine organisms.Therefore,a research must be conducted to find the solution for this problem.The feasibility of Fenton’s reagent to treat detergent waste was investigated in this study.The sample of detergent wastewater was taken from FPG Oleochemicals Sdn. Bhd.This experiment studied the effect of temperature towards the feasibility of Fenton’s reagent process besides the dosage between hydrogen peroxide (H2O2) and ferrous ion (Fe2+) in the reagent.While, evaluated efficiency of Fenton’s reagent in term of chemical oxygen demand (COD),total suspended solid (TSS) and the turbidity reduction within the experimental design.The result found that overall removal was achieved until 96.2% in term of COD, 98.1 % in term of TSS and 99.6 % in term of turbidity using Fenton’s reagent process.Besides,also found that this process is optimum at temperature 35oC able to achieve the Standard A of Parameter Limit of Effluent of Standard A & Standard B were outlined by Department of Environment based on Environment Quality Act 1974.